2018
DOI: 10.1186/s12977-018-0413-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 protease with leucine zipper fused at N-terminus exhibits enhanced linker amino acid-dependent activity

Abstract: BackgroundHIV-1 protease (PR) activation is triggered by Gag-Pol dimerization. Premature PR activation results in reduced virion yields due to enhanced Gag cleavage. A p6* transframe peptide located directly upstream of protease is believed to play a modulating role in PR activation. Previous reports indicate that the C-terminal p6* tetra-peptide prevents premature PR activation triggered by a leucine zipper (LZ) dimerization motif inserted in the deleted p6* region. To clarify the involvement of C-terminal p6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(38 reference statements)
2
3
0
Order By: Relevance
“…4 b; supplementary Fig. 4 b); this is consistent with previous reports [ 19 , 34 ]. We found that compared to the wt transfectant, cellular Pr55 gag was barely detectable in DWzPR and DWz/PR transfectants (Fig.…”
Section: Resultssupporting
confidence: 92%
“…4 b; supplementary Fig. 4 b); this is consistent with previous reports [ 19 , 34 ]. We found that compared to the wt transfectant, cellular Pr55 gag was barely detectable in DWzPR and DWz/PR transfectants (Fig.…”
Section: Resultssupporting
confidence: 92%
“…4b; supplementary Fig. 4b); this is consistent with previous reports [19,32]. We found that compared to the wt transfectant, cellular Pr55 gag was barely detectable in DWzPR and DWz/PR transfectants (Fig.…”
Section: Effects Of Enhanced Gag-pol Autocleavage On Pol Packagingsupporting
confidence: 92%
“…Previous studies have suggested that conserved C-terminal p6* tetrapeptide mutations trigger significant PR maturation impairment [ 10 , 20 , 21 ]. For the present study we focused on analyzing the effects of other conserved p6* residue mutations on virus processing and PR maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Single amino acid substitutions of the four C-terminal p6* residues can significantly impair virus maturation, strongly suggesting that the C-terminal p6* tetrapeptide is important for PR activation regulation [ 10 , 21 ]. Data from a study involving stepwise cluster substitutions for p6 codons (3–13 residues) suggest that both C- and N-terminal p6* regions are important, with the middle p6* part being largely dispensable in terms of PR activation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation